A nanosol SERS/RRS aptamer assay of trace cobalt(ii) by covalent organic framework BtPD-loaded nanogold catalytic amplification. Issue 13 (25th May 2021) - Wen, Guiqing; Xiao, Yang; Chen, Shuxin; Zhang, Xinghui; Jiang, Zhiliang
Abstract : A sensitive gold nanosol SERS/RRS aptamer assay of cobalt(ii ) based on AuBtPD catalytic amplification. Abstract : The determination of heavy metal ions has always been a hot topic in the field of environmental analysis. In this study, a new covalent organic framework-loaded gold nanoparticle (AuCOF) nanocatalytic amplification signal strategy was developed to determine trace Co 2+ in water. The COF of BtPD was synthesized from 1, 3, 5-benzene tricarboxaldehyde and p -phenylenediamine, and a new kind of AuBtPD nanosol was prepared by reduction of HAuCl4 to AuNPs on the BtPD carrier. It has strong catalysis of the new indicator reaction of sodium formate reducing HAuCl4 to AuNP sol with strong resonance Rayleigh scattering (RRS) at 370 nm and surface enhanced resonance Raman scattering (SERS) activity at 1614 cm −1 in the presence of a Victoria blue 4R (VB4R) molecular probe. Combining the nanocatalytic reaction to amplify the dual-scattering signals and specific aptamer (Apt) of cobalt ions, a new, fast, stable, sensitive and specific dual mode method for detecting Co 2+ was established; the RRS signal I 370nm and SERS signal I 1614cm −1 show a linear relationship with the concentration of 0.033–1 nmol L −1 Co 2+ and with a limit of detection (LOD) of 0.02 nmol L −1 . The two methods have been applied to the determination of Co 2+ in industrial wastewater, tap water and river water, and the results are satisfactory.